Roles of football team physician in the prevention and therapy of sports injuries - Stankov, Suncica; Stepančev, Bogdan (Medicinski časopis, 2023)
The football team physician roles includes an assessment and improving of general health of every member of a sports team, throughout implementation of prevention programmes and risk assessment of sports injuries. The important role of football team physician is pre-participation screening exam and reducing risk of sport injuries throughout formation of prevention strategies. The team physician implements the primary therapy and prevention of serious injuries and diseases which can cause fatal consequences to health status of football player. Different musculoskeletal diseases could be a result of injuries caused by playing a competitive football. First aid of these injuries provides the team doctor, by using adequate and initially therapy. Team physician organise daily supervision and cooperation with a players, which can lead to highly efficacious interventions in treatment and prevention of sport injuries, with goal to adequate monitoring of sports injuries.